Penamaan Busana Wanita pada Media Online Shop - Ely Irmawati; M. Rais Almajid; Ferdian Achsani (SUAR BETANG, 2020)
This study aims to determine the lexical meaning of the types of women's clothing and naming factors in the clothing itself. Because fashion is one of the things that are in great demand by women. The method used is a descriptive method by analyzing the meaning and naming factors of the types of lexical names in a market that are traded to consumers. The data collection technique used is to write and photograph. The data analysis is carried out in three stages, namely searching for data, managing data, and presenting data. The results of the study showed that the naming of the dresses was caused by various factors such as identity, similarity of features, abbreviations. The naming is classified in the category of naming 8 plants, 7 animals, 12 names of people representing, and 12 nouns. Naming clothes with names such as names of people, animals, plants and names of objects has the aim to give meaning to clothing products that are made according to the nature or character of the product name.